2007
DOI: 10.2140/pjm.2007.229.137
|View full text |Cite
|
Sign up to set email alerts
|

The Anosov theorem for infranilmanifolds with cyclic holonomy group

Abstract: A celebrated theorem of Anosov states that for any continuous self-map f : M → M of a nilmanifold M, the Nielsen number equals the Lefschetz number in absolute value. Anosov also showed that this result does not hold for infranilmanifolds, even in the simplest possible situation of flat manifolds with cyclic holonomy group.Nevertheless, in this paper we extend Anosov's theorem to infranilmanifolds with cyclic holonomy group, provided a certain easily checked condition on the holonomy representation is satisfie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This is precisely the condition on the holonomy representation of an infra-nilmanifold M with cyclic holonomy group under which the main result of [8] states that the Anosov theorem holds for M . Hence Theorem 3.7 generalises the main result of [8].…”
Section: A Contradiction With (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is precisely the condition on the holonomy representation of an infra-nilmanifold M with cyclic holonomy group under which the main result of [8] states that the Anosov theorem holds for M . Hence Theorem 3.7 generalises the main result of [8].…”
Section: A Contradiction With (B)mentioning
confidence: 99%
“…This criterion is a powerful tool in the generalisation of the Anosov theorem to certain classes of maps on infra-nilmanifolds or to certain classes of infra-nilmanifolds. For instance, it lies at the basis of the results in [7] and it is used in [8] to generalise the Anosov theorem to a well described class of infra-nilmanifolds with cyclic holonomy group.…”
mentioning
confidence: 99%
“…It was recently shown that for large families of flat manifolds (e.g. all flat manifolds with an odd order holonomy group) the Anosov relation N(f ) =| L(f ) | does hold for any self map (see [6] and [7]). It is therefore natural to ask.…”
Section: The Anosov Relation For Flat Manifolds and Entropy Conjecturementioning
confidence: 99%
“…It was first considered by Hantzsche and Wendt. From the other side the fundamental group π 1 (M 3 ) is group F (2,6), where F (r, n) is the group defined by the presentation…”
Section: Generalized Hantzsche-wendt Flat Manifoldsmentioning
confidence: 99%